2023
DOI: 10.3390/pharma2010005
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns of Antibiotics According to the WHO AWaRe Classification during the COVID-19 Pandemic at a Teaching Hospital in Lusaka, Zambia: Implications for Strengthening of Antimicrobial Stewardship Programmes

Abstract: Irrational and inappropriate prescribing of antibiotics is a major problem that can lead to the development of antimicrobial resistance (AMR). In Zambia, there is insufficient information on the prescribing patterns of antibiotics according to the World Health Organization (WHO) AWaRe classification. Therefore, this study assessed the prescribing patterns of antibiotics using the AWaRe classification during the COVID-19 pandemic at the University Teaching Hospital in Lusaka, Zambia. A cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 98 publications
3
18
1
Order By: Relevance
“…High levels of E. coli resistance to ampicillin and co-trimoxazole could be attributed to selective pressure resulting from misuse and overuse of antibiotics in the community and at primary healthcare facilities. 46 , 47 Comparable to our findings, a systematic review that analysed the prevalence of resistance to the top 10 antibiotics commonly prescribed in LMICs in commensal E. coli isolates from human sources in community settings found high resistance to ampicillin, co-trimoxazole and tetracycline. 48 Studies included in this systematic review were mostly from Asia ( n = 13) and Africa ( n = 10).…”
Section: Discussionsupporting
confidence: 79%
“…High levels of E. coli resistance to ampicillin and co-trimoxazole could be attributed to selective pressure resulting from misuse and overuse of antibiotics in the community and at primary healthcare facilities. 46 , 47 Comparable to our findings, a systematic review that analysed the prevalence of resistance to the top 10 antibiotics commonly prescribed in LMICs in commensal E. coli isolates from human sources in community settings found high resistance to ampicillin, co-trimoxazole and tetracycline. 48 Studies included in this systematic review were mostly from Asia ( n = 13) and Africa ( n = 10).…”
Section: Discussionsupporting
confidence: 79%
“… 31 , 94 , 124–126 Additionally, the high use of antibiotics could be attributed to increased prescribing of antibiotics in healthcare facilities. 127 , 128 The high use of antibiotics in healthcare facilities continues to be reported across the world. 129–132 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lack of awareness of the WHO AWaRe framework of antibiotics influences healthcare workers to prescribe and dispense antibiotics without following the guidelines, worsening the AMR challenge. 5 , 8 Another major challenge is limited resources and capacity to implement the framework in many countries, especially in lower- and middle-income countries. 9 Additionally, the low availability of affordable and good-quality antibiotics affects the sustainable implementation of the AWaRe system.…”
Section: Challenges Faced In Implementing the Who Aware Framework Of ...mentioning
confidence: 99%
“…In Zambia, there are gaps and lack of knowledge among healthcare workers on the use the AWaRe tool because studies have reported high prescribing of Watch antibiotics. 7 , 8 , 10 In all studies, ceftriaxone, a Watch antibiotic, was being overused (Table 1 ). This contrasts with the WHO recommendations.…”
Section: Experiences In Zambia On the Use Of The Aware Classification...mentioning
confidence: 99%